Answer:64
Step-by-step explanation:
Factor and solve the following equation 2x^2 + x - 21 = 0.
Answer:
x = -7/2 and 3
Step-by-step explanation:
Use foil. Solve for x.
Answer:
The factors are (2x + 7)(x - 3) and the solutions are -3.5 and 3
Step-by-step explanation:
* Lets explain how to factor a trinomial in the form ax² ± bx ± c:
- Look at the c term first.
# If the c term is a positive number, then its factors r , s will both
be positive or both be negative.
# a has two factors h and k
# The sum of c and a is b.
# The brackets are (hx ± r)(kx ± s) where a = hk , c = rs and b = rk + hs
# If the c term is a negative number, then either r or s will be negative,
but not both.
# a has two factors h and k
# The difference of c and a is b.
# The brackets are (hx + r)(kx - s) where a = hk , c = rs and b = rk - hs
* Lets solve the problem
∵ The equation is 2x² + x - 21 = 0
∵ The general form of the equation is ax² + bx + c = 0
∴ a = 2 , b = 1 , c = -21
∵ c is negative
∴ its factors r and s have different sign
∵ a = 2
∵ The factors of a are h , k
∵ 2 = 2 × 1
∴ h = 2 and k = 1
∵ -21 = 7 × -3
∴ r = 7 and s = -3
∵ The brackets are (hx + r)(kx - s)
∴ 2x² + x - 21 = (2x + 7)(x - 3)
∵ 2x² + x - 21 = 0
∴ (2x + 7)(x - 3) = 0
- Equate each bracket by 0
∴ 2x + 7 = 0 ⇒ subtract 7 from both sides
∴ 2x = -7 ⇒ divide both sides by 2
∴ x = -7/2 = -3.5
- OR
∴ x - 3 = 0 ⇒ add 3 to both sides
∴ x = 3
∴ The solutions are -3.5 and 3
* The factors are (2x + 7)(x - 3) and the solutions are -3.5 and 3
What is the standard form for the quadratic function? g(x)=(x+1)^2−2
g(x)=x^2−2x−4
g(x)=x^2−1
g(x)=x^2+2x−1
g(x)=x^2−3
the standard form is g(x)=x^2+2x-1
what is the simplified version of the fraction below? 24/30
Answer:
4/5
Step-by-step explanation:
The prime factorization of 24 is 2*2*2*3.
There prime factorization of 30 is 2*3*5.
They have 2*3 in common.
2*3=6.
So we can divide numerator (top) and denominator (bottom) by 6 and this will reduce the fraction into simplest form.
[tex]\frac{24}{30}=\frac{24 \div 6}{30 \div 6}=\frac{4}{5}[/tex]
The simplified version of the fraction 24/30 is 4/5
What is fraction ?Fraction is a mathematical number by which we can describe a part of a whole item.
A fraction has two parts, the top part is called numerator & the bottom part is called denominator.
Example : [tex]\frac{5}{7}[/tex] , where 5 is the numerator & 7 is the denominator.
What is the required fraction ?The given fraction is 24/30
The prime factorisation of 24 gives 2×2×2×3 , i.e. 2×2×(2×3)
The prime factorisation of 30 gives 2×3×5 , i.e. 5×(2×3)
Common in both 24 & 30 is 2×3, i.e. 6
So, we have to divide numerator & denominator of the given fraction by 6 to get the simplified form.
Hence, 24/30 = (24/6)/(30/6) = 4/5
Learn more about fraction here :
https://brainly.com/question/1622425
#SPJ2
in the currency pair USD/CAN, USD is the ____ ?
In the currency pair USD/CAN, USD is the base currency. The value of this base currency is always one unit. The relation between the pair demonstrates the concept that when one currency strengthens, the other weakens.
Explanation:In the currency pair USD/CAN, USD is the base currency. It is then compared to the other currency, called the quote or counter currency, in this case, the Canadian dollar (CAN). The base currency is always worth one unit, and the exchange rate you see tells you how much of the counter currency it takes to buy one unit of the base currency. A fall in the Canada $/U.S. $ ratio means a rise in the U.S. $/Canada $ ratio, demonstrating the idea that the appreciation or strengthening of one currency often implies the depreciation or weakening of the other.
Learn more about Currency Pair here:https://brainly.com/question/28453299
#SPJ12
In the currency pair USD/CAN, USD is the base currency.
Explanation:Currency refers to a system of money used in a specific country or region, including coins and banknotes. It serves as a medium of exchange for goods and services. Currencies have different denominations and exchange rates, facilitating economic transactions within their respective jurisdictions.
In the currency pair USD/CAN, USD is the base currency. In a currency pair, the base currency represents the value of one unit of that currency in terms of the other currency. In this case, the USD/CAN currency pair means that 1 USD is equivalent to a certain amount of Canadian dollars. For example, if the exchange rate is 1 USD = 1.25 CAD, it means that 1 USD can be exchanged for 1.25 Canadian dollars.
Learn more about Currency pair here:https://brainly.com/question/28453299
#SPJ12
The mean score on a set of 27 tests is 78. Suppose two more students take the test and score 69 and 66. What is the new mean?
Answer:
77.3 to the nearest tenth.
Step-by-step explanation:
The total of the scores on the set of 27 tests
= 78*27 = 2106.
After 2 more had joined the total score is 2106 + 69 + 66
= 2241.
So the new mean score = 2241 / 29
= 77.3.
Answer:
77.3
Step-by-step explanation:
Recall that the arithmetic mean is found as follows:
sum of all data
a. m. = ---------------------------
number of data
sum
The mean score of 27 test results is thus 78 = --------
27
Note that we can find the sum of all 27 of the original scores by multiplying 78 by 27: 2106.
Now we include two more scores. Instead of the original sum, 2106, we have
2106 + 69 + 66
a. mean = ---------------------------
29
which comes out to 2241/29 = 77.3
SOMEONE PLEASE HELP I NEED TO KNOW AND IVE BEEN ASKING THIS FOR 10 MINUTES
Roopesh has $24 dollars to spend on a birthday gift. The store where he is shopping has a sale offering $5 off the regular price, r, of any item. Write an inequality that can be used to determine the regular price of an item in the store that Roopesh can afford. (Assume there is no tax.)
What is the unknown?
Which expression can represent the sale price?
Which comparison could be used?
Which inequality represents the situation?
Answer:
r ≤ 29, r-5, The sale price can be compared with the regular price, r-5 ≤ 24
Step-by-step explanation:
Amount to spend = $24
Regular price = r
Sale = $5
Sale Price = r-5
The regular price will be at most $5 more than the amount Roopesh has to spend.
The sale price will be $24 or less than that for Roopesh to afford.
Inequality for regular price :
r-5 ≤ 24
r ≤ 29
Therefore, the product Roopesh can afford is $29 or less than that.
What is the unknown? r ≤ 29
Which expression can represent the sale price? Sale price = r-5 (mentioned above)
Which comparison could be used? The sale price can be compared with the regular price
Which inequality represents the situation? r-5 ≤ 24
!!
(x-2)(-5x^2+x)=(x)(-5x^2)+(x)(x)+(-2)(-5x^2)+(-2)(x)
Answer:
Step-by-step explanation:
First we will solve the Left Hand Side:
(x-2)(-5x²+x)
Multiply the terms:
= -5x³+x²+10x²-2x
Solve the like terms
= -5x³+11x²-2x
Now we will solve the Right Hand Side:
(x)(-5x²)+(x)(x)+(-2)(-5x²)+(-2)(x)
Multiply the terms:
-5x³+x²+10x²-2x
Solve the like terms:
-5x³+11x²-2x
Hence it is proved that L.H.S = R.H.S....
Write ln2x+2lnx-ln3y as a single logarithm.
a. ln(2x/3y)
b. ln(3x/3y)
c. ln(2x^3/3y)
d. ln(x^3/3y)
Answer is C. ln(2x^3/3y) on Edge!
Answer:
Option C. [tex]ln(\frac{2x^{3}}{3y})[/tex]
Step-by-step explanation:
The given logarithmic expression is:
[tex]ln(2x)+2ln(x)-ln(3y)[/tex]
Using the power rule of logarithms: [tex]blog(a)=log(b)^{a}[/tex], the above expression can be written as:
[tex]ln(2x)+ln(x)^{2}-ln(3y)[/tex]
Using the product rule of logarithms: [tex]log(a)+log(b) =log(ab)[/tex], the above expression can be simplified further to:
[tex]ln(2x \times x^{2}) - ln(3y)\\\\=ln(2x^{3})- ln(3y)[/tex]
Using the quotient rule of logarithms: [tex]log(a)-log(b)=log(\frac{a}{b})[/tex], the above expression can be written as:
[tex]ln(\frac{2x^{3}}{3y})[/tex]
Hence option C gives the correct simplified answer.
What is the probability of not drawing a red marble?
5/5
3/5
50%
30%
Answer:
50%
Step-by-step explanation:
There are 10 marbles total in the bag, and 5 of them are red. So, to find the probability of not drawing a red marble, you need to count how many marbles are not red.
There are 3 green marbles and 2 blue marbles so there are 5 marbles that are not red.
So you need to write this as a fraction so 5/10 of the marbles are not red.
None of the answer choices that are fractions match 5/10 or 1/2, so you need to convert 5/10 to a percent.
To convert it as a percent you divide 5 by 10, which is .50
Then you move the decimal point two places to the right so its 50%
So there is a 50% percent chance of not drawing a red marble.
The set of possible values of n is {-2, 1; 4).
What is the set of possible values of m if
3m = n-7?
How do I solve it
Replace n in the equation with each given value and solve for m.
You are given n = {-2, 1, 4}
When n = -2:
3m = -2-7
3m = -9
m = -9/3
m = -3
When n = 1:
3m = 1-7
3m = -6
m = -6 /3
m=-2
When n = 4:
3m = 4-7
3m = -3
m = -3/3
m = -1
m = {-3, -2, -1}
Which of the following are remote interior angles of _1? Check all that apply.
Answer:
B and E
Step-by-step explanation:
The remote interior angles to ∠1 are the 2 opposite interior angles, that is
∠5 and ∠6
Which of the following is best described as a pair of opposite angles formed
by intersecting lines?
O
A. Vertical angles
O
B. Supplementary angles
O
O
C. Complementary angles
D. Linear pair
Answer:
Vertical angles
Step-by-step explanation:
Vertical angles are the angles that happen opposite to each other in two intersecting lines. (These angles are congruent.)
Supplementary means that the two angles add up to be 180.
Complementary means the two angles add up to 90.
Linear pair are supplementary adjacent angles. (Adjacent means next to sharing the same vertex and a common ray.)
The given statement is the definition of vertical angles.
What are vertical angles?Vertical angles are either of two angles lying on opposite sides of two intersecting lines.
What are Supplementary angles?Supplementary angles are two angles whose sum is 180 degrees.
What are Complementary angles?Complementary angles are two angles whose sum is 90 degrees.
What are Linear pair?Linear pair of angles are formed when two lines intersect each other at a single point.
How to find which of the following is best described as a pair of opposite angles formed by intersecting lines?In the question, it is given to describe two angles as a pair of opposite angles formed by intersecting lines.According to the definition, these are vertical angles, which two angles lying on opposite sides of two intersecting lines.
Find more about "Vertical angles" here: https://brainly.com/question/14362353
#SPJ2
what is the total surface area of the rectangular pyramid below
Answer:
S.A. = 225 ft²Step-by-step explanation:
We have
the rectangle 12ft × 6ft
two triangles with the base b = 12ft and the height h = 8ft
two triangles with the base b = 6ft and the height h = 9.5ft.
The formula of an area of a rectangle l × w:
[tex]A=lw[/tex]
Substitute:
[tex]A_1=(12)(6)=72\ dt^2[/tex]
The formula of an area of a triangle:
[tex]A=\dfrac{bh}{2}[/tex]
Substitute:
[tex]A_2=\dfrac{(12)(8)}{2}=48\ ft^2[/tex]
[tex]A_3=\dfrac{(6)(9.5)}{2}=28.5\ ft^2[/tex]
The Surface Area:
[tex]S.A.=A_1+2A_2+2A_3[/tex]
Substitute:
[tex]S.A.=72+2(48)+2(28.5)=225\ ft^2[/tex]
Answer:
Total surface area of the pyramid = 225 ft²
Step-by-step explanation:
Total surface area of the given pyramid is defined by
(Area of rectangular base) + 2(area of two triangular sides with height 8 ft and base 12 ft) + 2(area of two triangles with height 9.5 ft and base 6 ft)
Total surface area = (12×6) + 2[[tex]\frac{1}{2}\times(h)(b)[/tex]]+2[[tex]\frac{1}{2}\times(h')(b')[/tex]]
= 72 + 2[[tex]\frac{1}{2}\times(8)(12)[/tex]]+2[[tex]\frac{1}{2}\times(9.5)(6)[/tex]]
= 72 + 96 + 57
= 225 ft²
Therefore, total surface area of the pyramid is 225 ft²
There were 24 acts performing in
the talent show. Eight acts were
solo performances and the rest
were performed by a group. What
percent of the acts were group
performances?
F. 30%
G. 33 1/3 %
H. 60%
I. 66 2/3%
Find the total number of groups by subtracting the solo acts from the total acts:
24 - 8 = 16 group acts.
Now divide the number of group acts by the total number of acts:
16 /24 = =0.666
Multiply by 100:
0.666 x 100 = 66.6% = 66 2/3%
The answer is I.
PLEASE HELP ME!!! what are the roots of x in -10x^2+12x-9=0
Answer:
Option B.
Step-by-step explanation:
We have the following polynomial: -10x^2+12x-9=0
Multiplying by -1:
10x^2-12x+9=0
Using the quadratic formula, we find that the roots are:
0.6 ± 3√(6)/10i
Therefore, the correct answer is B.
In the figure Triangle BAT is congruent to Triangle CAT. Which statement is true by CPCTC?
Answer:
BT is Congruent to CT
Step-by-step explanation:
Since these two triangles are said to be congruent, that means that their side lengths and angle measures are congruent as well. So, since BT corresponds to CT in the diagram, they must be congruent.
Answer:
BT≅CT
Step-by-step explanation:
If two triangles are congruent it means that they have the same size and shape, or that they mirror each other. Since the side, AT, is common to both triangles, the congruent triangles are mirrored in this case, which means that side CT in ∠CAT corresponds to side BT in ∠BAT.
A discrete randem variable is a variable that is randomly chosen and can only take on certain values.
A. True
B. False
Answer:
A. True.
Step-by-step explanation:
For example, the results of throwing a fair dice. The variable can only be 1,2,3,4,5,6.
Answer: True
A P E X
A discrete randem variable is a variable that is randomly chosen and can only take on certain values.
What is the value of in the equation 5x+3=4x
Answer:
- 3
Step-by-step explanation -
- 5x from both sides -> 3 = -1x .
then divide each side by - 1 -> -3 = x
Answer:
-3
Step-by-step explanation:
5x+3=4x
Subtract 5x on both sides.
5x+3-5x=4x-5x
Simplify.
3=-1x
3=-x
Take opposite of both sides.
-3=x
x=-3
Help please!!!
What is the distance between the two endpoints in the graph below? If necessary, round your answer to two decimal places.
Answer:
A) 7.07
Step-by-step explanation:
[tex]The \: distance \: formula = \sqrt{(x_2 - x_1) ^{2} + (y_2 - y_1) ^{2} } [/tex]
[tex]P_1(-3, -2) \: \: \: \: \: \: \: \: \: \: \: P_2(2, 3)[/tex]
[tex]d = \sqrt{ {(2 - ( - 3))}^{2} + {(3 - ( - 2))}^{2} } \\ d = \sqrt{ {(2 + 3)}^{2} + {(3 + 2)}^{2} } \\ d = \sqrt{ {5}^{2} + {5}^{2} } \\ d = \sqrt{25 + 25} \\ d = \sqrt{25(1 + 1)} \\ d = \sqrt{25(2)} \\ d = \sqrt{25} \times \sqrt{2} \\ d = 5 \sqrt{2} \\d = 7.07106781187 \\ d = 7.07[/tex]
Answer: A. 7.07 units
Step-by-step explanation:
The distance between any two points (a,b) and (c,d) is given by :-
[tex]D=\sqrt{(d-b)^2+(c-a)^2}[/tex]
From the given picture , we can see that the line is passing through (2,3) and (-3,-2).
The distance between (2,3) and (-3,-2) is given by :-
[tex]D=\sqrt{(-2-3)^2+(-3-2)^2}\\\\\Rightarrow\ D=\sqrt{(-5)^2+(-5)^2}\\\\\Rightarrow\ D=\sqrt{25+25}=\sqrt{50}\\\\\Rightarrow\ D=7.07106781187\approx7.07[/tex]
Hence, the distance between the two endpoints = 7.07 units
Let f(x) = -2x - 7 and g(x) = -4x + 6. Find (fxg)(-5).
Answer:
78
Step-by-step explanation:
Multiply f(x) and g(x) then evaluate for x = - 5
f(x) × g(x)
= (- 2x - 7)(- 4x + 6) ← substitute x = - 5 into the expression
= (10 - 7)(20 + 6)
= 3 × 26
= 78
For this case we have the following functions:
[tex]f (x) = - 2x-7\\g (x) = - 4x + 6[/tex]
We must find [tex](f * g) (x).[/tex] By definition we have to:
[tex](f * g) (x) = f (x) * g (x)[/tex]
So:
[tex](f * g) (x) = (- 2x-7) (- 4x + 6)[/tex]
We apply distributive property keeping in mind that:
[tex]- * - = +\\- * + = -\\(f * g) (x) = 8x ^ 2-12x + 28x-42\\(f * g) (x) = 8x ^ 2 + 16x-42[/tex]
We evaluate in [tex]x = -5[/tex]:
[tex](f * g) (- 5) = 8 (-5) ^ 2 + 16 (-5) -42\\(f * g) (- 5) = 8 * 25-80-42\\(f * g) (- 5) = 200-80-42\\(f * g) (- 5) = 78[/tex]
Answer:
[tex](f * g) (- 5) = 78[/tex]
a. Find the length of the midsegment of an equilateral triangle with side lengths of 12.5 cm.
b. Given that UT is the perpendicular bisector of AB, where T is on AB, find the length of AT given AT = 3x + 6 and TB = 42 - x.
c. Given angle ABC has angle bisector BD, where AB = CB, find the value of x if AD = 5x + 10 and DC = 28 - x.
Answer:
a) The length of the mid-segment is 6.25 cm
b) The length of AT = 33 units
c) The value of x is 3
Step-by-step explanation:
a)
* Lets explain the mid-segment of a triangle
- A mid-segment of a triangle is a segment connecting the midpoints
of two sides of a triangle
- This segment has two special properties
# It is parallel to the third side
# The length of the mid-segment is half the length of the third side
∵ The triangle is equilateral triangle
∴ All sides are equal in length
∵ the side lengths = 12.5 cm
∵ The length of the mid-segment = 1/2 the length of the third side
∴ The length of the mid-segment = 1/2 × 12.5 = 6.25 cm
* The length of the mid-segment is 6.25 cm
b)
∵ UT is a perpendicular bisector of AB
∵ T lies on AB
∴ T is the mid-point of AB
∵ AT = BT
∵ AT = 3x + 6
∵ BT = 42 - x
- Equate AT and BT
∴ 3x + 6 = 42 - x
- Add x to both sides
∴ 4x + 6 = 42
- Subtract 6 from both sides
∴ 4x = 36
- Divide both sides by 4
∴ x = 9
∵ AT = 3x + 6
- Substitute x by 9
∴ AT = 3(9) + 6 = 27 + 6 = 33
* The length of AT = 33 units
c)
- In Δ ABC
∵ AB = BC
∴ Δ ABC is an isosceles triangle
∵ BD bisects angle ABC
- In the isosceles Δ the bisector of the vertex angle bisects the base
of the triangle which is opposite to the vertex angle
∵ AC is the opposite side of the vertex B
∴ BD bisects the side AC at D
∴ AD = CD
∵ AD = 5x + 10
∵ CD = 28 - x
∴ 5x + 10 = 28 - x
- Add x to both sides
∴ 6x + 10 = 28
- Subtract 10 from both sides
∴ 6x = 18
- Divide both sides by 6
∴ x = 3
* The value of x is 3
The true statements are:
a) The length of the midsegment is 6.25 cm
b) The length of AT = 33 units
c) The value of x is 3
The length of the midsegment
The length of the triangle is given as
L =12.5cm
So, the length of the midsegment is:
M = 0.5 * L
This gives
M = 0.5 * 12.5 cm
M = 6.25 cm
Hence, the length of the midsegment is 6.25 cm
The length of AT
The given parameters are:
AT = 3x + 6 and TB = 42 - x.
Since point T is the perpendicular bisector, then we have:
3x + 6 = 42 - x
Collect like terms
3x +x = -6 + 42
Evaluate
4x = 36
Divide both sides by 4
x = 19
Recall that:
AT = 3x + 6
So, we have:
At = 3 * 9 + 6
At = 33
Hence. the length of AT = 33 units
The value of x
We have:
AD = 5x + 10
DC = 28 - x
So, we have:
5x + 10 =28 - x
Collect like terms
5x + x = 28 -10
6x =18
Divide
x =3
Hence, the value of x is 3
Read more about lengths at:
https://brainly.com/question/19819849
Dru is constructing a bridge. It takes 12 cubic yards of concrete to make a bridge that is
4 inches thick.
20. Write a direct variation equation that relates c and t, where c is cubic yards of concrete and t
is thickness in inches.
also, How many cubic yards of concrete does Dru need to make the bridge 6 inches thick?
Answer:
c=3t is the equation
18 cubic yards of concrete is what we need for a 6 inch thick bridge.
Step-by-step explanation:
If something directly varies, that means there is a constant, k, such that when you multiply it to one variable you always get the other variable.
That is for this particular problem we have c=kt where c is cubic yards and t is thickness in inches.
So we are given from the first sentence: 12 cubic yards and 4 inches thick which means we have:
12=k(4)
Divide both sides by 4:
12/4=k
Simplify:
3=k
So the equation is c=3t for any point (c,t) in this relation.
So we want to know many cubic yards of concrete (we want to know (c) so that Dru can build a 6 inch (t) thick bridge.
c=3(6)
c=18
18 cubic yards
Five men can install 200 yards of pipeline in an eight hour day three men are added to the job assuming the individuals rates remain the same how many days will it take the entire crew to install 2240 yards of pipeline
Answer:
7 days
Step-by-step explanation:
Five men do 200 yards in one day
One man does 200/5 = 40 yards in 1 day.
=============
Now you want to know something about 8 men
8 men can do 40 * 8 = 320 yards in 1 day
=============
2240 yards / 320 yards = 7 days
URGENT,PLEASE HELP ME !!!!!!!!!!!!!!!
Answer: The last one
Step-by-step explanation:
I think this because the graph starts from H the number of hours studied and when u add the numbers and divide them up which gives you the equation 65 + 50 . Any questions please text me. Have a nice day.
Which of the following solids has a triangular cross section when the cross section is taken perpendicular to the base?
A.
square pyramid
B.
cube
C.
hexagonal prism
D.
rectangular prism
Answer:
A. square pyramid
Step-by-step explanation:
A square pyramid has a triangular cross section when the cross section is taken perpendicular to the base.
The solid that has a triangular cross section when the cross section is taken perpendicular to the base is a square pyramid. A cross section through the sloping triangular faces of the square pyramid will reveal a triangular shape.
To answer this, consider the properties of each option:
A square pyramid has a square base and triangular faces that meet at a common point above the base, resembling a series of tetrahedra joined together. When a cross section is taken perpendicular to its square base, it would indeed reveal a triangle shape as it would pass through these sloping triangular faces.
A cube would not result in a triangular cross section since it has all square faces.
A hexagonal prism has a hexagon as its base, and taking a cross section perpendicular to this base would yield a hexagon, not a triangle.
Similarly, a rectangular prism would result in a rectangle or square from such a cross section.
Therefore, the correct answer is a square pyramid.
Complete: 45° C = ___° F
A. 81 B. 77 C. 25 D. 13
Answer:
113ºF
Step-by-step explanation:
Remember that exist a conversion rule that states:
[tex]F=\frac{9*C}{5} +32[/tex]
using it we have the following expression:
[tex]1.8*(45)+32=113[/tex]
Solve the system of equations.
y= 2x + 4
y = x2 + x - 2
Answer:
A.
Step-by-step explanation:
[tex]y=2x+4[/tex]
[tex]y=x^2+x-2[/tex]
Both equations are solved for y so I'm just going to substitute
the 1st y (the 2x+4) into the second equation's y.
[tex]2x+4=x^2+x-2[/tex]
I'm going to get everything on one side so I have 0=ax^2+bx+c.
Subtract 2x and subtract 4 on both sides:
[tex]0=x^2-x-6[/tex]
Since the coefficient of x^2 is 1, all we have to do is find two numbers that multiply to be -6 and add up to be -1.
These numbers are -3 and 2.
So the factored form of our equation is:
[tex]0=(x-3)(x+2)[/tex]
This means we have x-3=0 or x+2=0.
x-3=0
Add 3 on both sides:
x=3
x+2=0
Subtract 2 on both sides:
x=-2
So now we need to find y. I'm going to choose to use the easier equation:
y=2x+4.
If x=3, then y=2(3)+4=6+4=10. The ordered pair (3,10) is a solution.
If x=-2, then y=2(-2)+4=-4+4=0. The orded pair (-2,0) is a solution.
(3x-5)+(15-x)+(2x-3)
The perimeter is 35 ft.
Answer:
17x
Step-by-step explanation:
combine like terms,you would end up with 20x because if you combine 3x and 2x=5 then 5x+15x is 20x.then 20x-3 is 17x.
what is the gcf of 42 and 60
Answer:
The GCF of 42 and 60 is 6
Step-by-step explanation:
42: 1,2,3,6,7,14,21,42
60: 1,2,3,4,5,6,10,12,15,20,30,60
Answer:
6
Step-by-step explanation:
Factors of 42 = 1, 2, 3, 6, 7, 14, 21 and 42
Factors of 60 = 1 , 2 , 3 , 4 , 5 , 6 , 10 , 12 , 15 , 20 , 30 and 60
The highest factor which comes in both 42 and 60 is 6
What polynomial has roots of −6, 1, and 4?
x3 − 9x2 − 22x + 24
x3 − x2 − 26x − 24
x3 + x2 − 26x + 24
x3 + 9x2 + 14x − 24
Answer:
The correct option is C
Step-by-step explanation:
We have given the roots -6, 1 and 4.
Write down the roots:
x= -6 , x=1 , x=4
Rewrite the roots as an expression:
x+6=0
x-1=0
x-4=0
Now we have the following expressions:
=(x+6)(x-1)(x-4)
Now Multiply the terms:
=(x²-x+6x-6)(x-4)
=(x²+5x-6)(x-4)
=x(x²+5x-6) -4(x²+5x-6)
=x³+5x²-6x-4x²-20x+24
Solve the like terms:
=x³+x²-26x+24
Thus the correct option is C....
Answer:
aaaaaaaa top one wrong
Step-by-step explanation: